Complementary versus companion diagnostics: apples and oranges?. (January 2015) - Milne, Christopher-Paul; Bryan, Crystal; Garafalo, Steven; McKiernan, Marie
There have been several major problems that have plagued biopharmaceutical development since the end of the 1990s, but two in particular have reached the point where they are impacting the economic viability of the industry: the lack of efficacy of new drugs and increasing competition among therapeutics that broadly attack certain common diseases and disease areas. The US FDA has noted that the era of one-size-fits-all treatment may well be reaching its end days as companies increasingly adopt approaches that involve biomarkers (there are now commercial databases that purport to track over 11, 000 of them). Pharmacogenomic biomarkers in particular are used to create diagnostics that help to differentiate or stratify the likely outcomes a patient will experience with a drug, which can now be said to be targeted or tailored to patients with particular traits (i.e., personalized), leading to an era of so-called precision medicine. As more is understood about diseases and the why and how of their effects on people through advances in biomarkers and genomics, personalized medicine is becoming a natural result of biomedical science and a natural trajectory for the innovation-based biopharmaceutical industry. The focus of this article is to examine an apparent divergence in that trajectory engendered by a growing differentiation in the approaches to personalized medicines in terms of their accompanying diagnostics: companion diagnostics are typically linked to a specific drug within its approved label, while complementary diagnostics are associated more broadly, usually not with a specific drug but with a class of drugs, and not confined to specific uses by labeling, with consequent ramifications for economic, regulatory and strategic considerations.